2019
DOI: 10.1111/add.14819
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural social support, substance use and sexual orientation from a nationally representative sample of US adults

Abstract: Background and Aims Sexual minority (SM) populations experience higher rates of substance use disorder (SUD) associated with increased sexual orientation‐related stress. Social support may moderate the impact of stress on SUD among SM adults. This study assessed associations between social support and DSM‐5 SUD by sex and sexual minority identity. Design Cross‐sectional study using data from the 2012–13 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC‐III). Setting and participants A nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…The current results provide compelling evidence for gender differences in the multifactorial factors underlying CUD in adults, which had not been previously investigated using a multi-domain approach. We are only aware of one previous study on gender differences in CUD in adults (81). This study specifically investigated gender differences in the role of social support and found a stronger protective relationship of social support in women as compared to men (81).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results provide compelling evidence for gender differences in the multifactorial factors underlying CUD in adults, which had not been previously investigated using a multi-domain approach. We are only aware of one previous study on gender differences in CUD in adults (81). This study specifically investigated gender differences in the role of social support and found a stronger protective relationship of social support in women as compared to men (81).…”
Section: Discussionmentioning
confidence: 99%
“…We are only aware of one previous study on gender differences in CUD in adults (81). This study specifically investigated gender differences in the role of social support and found a stronger protective relationship of social support in women as compared to men (81). Additionally, our results extend previous findings on cannabis use in adolescence that suggest a stronger influence of environmental factors in girls as compared to boys (8285).…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies that have examined whether the protective effect of marriage on alcohol use differs by sexual identity have yielded mixed results. For example, one recent U.S. study found marriage was associated with lower odds of alcohol use disorder and drug use disorder among heterosexual women and men, but not among SMW or SMM (Kahle et al, 2020). By contrast, other U.S. studies have found that both same-sex and different-sex married couples reported lower alcohol use than their cohabiting non-married counterparts (Reczek et al, 2014).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 95%
“…The Official Journal of the Kettil Bruun Society for Social and Epidemiological Research on Alcohol ------IJADR 8(2) ------hazardous drinking or to use marijuana than those who are not, including those who are cohabiting, single, or divorced/separated (Blair & Menasco, 2016;Jang, Patrick, & Schuler, 2018;Kahle, Veliz, McCabe, & Boyd, 2020;Li, Wilsnack, Wilsnack, & Kristjanson, 2010;Liang & Chikritzhs, 2012;Reczek, Liu, & Spiker, 2014). Protective effects of marriage are linked to a variety of factors, including marital partners' influences on each other's health habits, greater social support, and lower general stress (Umberson & Karas Montez, 2010).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…Family support, especially for adolescents in long term residential programs has been proven to be necessary for successful recovery from addiction [66]. Studies have also showed that having a strong social and family resource improves the chances of addiction recovery [67][68][69][70]. Self-development efforts encompassing activities that lead to mental and physical well-being, such as regular exercise, meditation, and yoga have been observed to help heal the body and mind [71,72].…”
Section: The Sem Model For Recoverymentioning
confidence: 99%